2015
DOI: 10.1039/c5tb00158g
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-coated electrospun nanofibers with antibacterial activity

Abstract: Charged nanofibers were prepared by electrospinning (ESP) poly(e-caprolactone) with a copolymer bearing carboxylic acid functions. The presence of these functions allowed exposing some negative charges on the fiber surface, by dipping the fibers in a phosphate buffer. A layer of chitosan, a polycation in acidic medium, was then deposited on the nanofiber surface, thanks to electrostatic attraction. Fibers were characterized at each step of the process and the influence of the copolymer architecture on chitosan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…On the other hand several authors have reported SZP results for various material types ( [13][14][15][16][17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35] ) obtained by the EOF method (in different congurations) using mostly polymeric tracer particles. The problems observed in these studies were associated with a high measurement uncertainty that consequently lowers the quality of the data 15,16,24,27,[38][39][40] especially for more complex sample surfaces (nanobers, membranes), difficulties in determining the surface IEP when oppositely charged tracer particles were exposed, 15,18,19,26,29 or the observation of polymeric tracer particles sedimentation and degradation (colour change of tracer particle dispersion), which is even more pronounced under elevated ionic strength, 15,19,24,28 that limits the applicability of the EOF method at high salinity conditions. Moreover, results from the EOF method showed also bad reproducibility and questionable reliability.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand several authors have reported SZP results for various material types ( [13][14][15][16][17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35] ) obtained by the EOF method (in different congurations) using mostly polymeric tracer particles. The problems observed in these studies were associated with a high measurement uncertainty that consequently lowers the quality of the data 15,16,24,27,[38][39][40] especially for more complex sample surfaces (nanobers, membranes), difficulties in determining the surface IEP when oppositely charged tracer particles were exposed, 15,18,19,26,29 or the observation of polymeric tracer particles sedimentation and degradation (colour change of tracer particle dispersion), which is even more pronounced under elevated ionic strength, 15,19,24,28 that limits the applicability of the EOF method at high salinity conditions. Moreover, results from the EOF method showed also bad reproducibility and questionable reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have studied the incorporation of major biopolymers in PCL through coating or blending. It is conducted through collagen [12,13,23,26], or its denatured form, gelatin [10,27], and chitosan as a natural polysaccharide [14,28,29], or a blend of chitosan-gelatin [30]. In this work, a blend of both collagen and chitosan was coated onto the surface of electrospun PCL samples, and, to the best of the author's knowledge, this is the first study to use them as a blend for grafting on electrospun PCL mats.…”
Section: Discussionmentioning
confidence: 99%
“…After coating scaffolds with the chitosan through electrostatic interactions, they did not observe any growth of bacterial colonies in the chitosan-coated mats [14]. Ezhilarasu et al investigated loaded PCL/aloe Vera (AV) blends with curcumin (CUR) and tetracycline hydrochloride (TCH), separately, using electrospinning technique to compare their effects and reported better antibacterial activity and surface wettability for PCL/TCH in comparison with PCL/AL, which could be helpful in wound healing applications [15].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…There is also a high number of research papers that have developed composite chitosan-containing nanofibers for other biomedical applications: nanofibers of chitosan/polyethylene oxide for cartilage tissue engineering [88], chitosan/polyvinyl alcohol nanofibers for oral candidiasis treatment [89,102] and poly(ε-caprolactone)-poly(ethylene glycol) copolymer nanofibrous mats that were incorporated into chitosan for the regeneration of periodontium [90]. An interesting multitude of nanocomposite materials have been fabricated for wound healing applications: chitosan/polyethylene oxide nanofibers [91,103], poly(ε-caprolactone)/chitosan nanofibers [92,104,105], chitosan/polyvinyl alcohol nanofibers [93,106,107], chitosan/collagen nanofibrous membranes [94], chitosan hydrogel/nanofibrin composite [95], chitosan/sericin-nanofibers [96], chitosan-Eudragit nanofibrous sheets [97], chitosan/arginine nanofibrous membrane [98], chitosan/gelatin/shape memory polyurethane nanofibers [99] or tannic acid/chitosan/pullulan composite nanofibers [100].…”
Section: Main Organic Nanomaterials Used In the Dental Fieldmentioning
confidence: 99%